Determinants of neonatal hypoglycemia among neonates admitted to neonatal intensive care units of public hospitals in Wolaita Zone, Southern Ethiopia, 2023: An unmatched case–control study - Wodajo, Dawit Tesfaye; Gebretsadik, Woiynshet; Melketsedik, Zeleke Aschalew; Desalegn, Nathan; Lencha, Fikre Moga (Frontiers in Pediatrics, 2024)
Background: Globally, neonatal hypoglycemia is a common child health problem and significantly contributes to morbidity and mortality, with its impact being particularly detrimental in developing countries. Although being a prevalent metabolic condition, it is frequently overlooked. Furthermore, the problem is not adequately studied in Ethiopia as seen by a few of published studies on the topic, which highlights the lack of knowledge about its determinants.Objective: -To assess the determinants of neonatal hypoglycemia among neonates admitted to NICU at public hospitals in Wolaita Zone, Southern Ethiopia, 2023. Methods: -An institution based unmatched case-control study design was conducted among 249 (83 cases and 166 controls). Data were collected from March 29 to May 23, 2023, using pretested chart review extraction tool/checklist. A consecutive sampling method was used for participant selection. Data were analyzed using SPSS version 25. Binary logistic regression analysis was used to identify the determinants of neonatal hypoglycemia and statistical significance was declared at P<0.05.Result: -A total of 83 cases and 166 controls were included in the study. Preterm neonates [AOR 4.888 (1.113, 21.478)], age of the neonate at admission (3-5 hours) [AOR 4.205 (1.852, 9.547)],hypothermia [AOR 5.485 (2.360, 12.748)], late initiation of breastfeeding [AOR 6.229 (2.665, 14.599)], mode of delivery [AOR 5.034 (1.688, 15.011)], and small for gestational age [AOR 3.645 (1.286, 10.330)] were significantly associated with neonatal hypoglycemia.In the current study, numerous determinants of neonatal hypoglycemia have been identified. Therefore, it is crucial to give due emphasis to providing comprehensive health education to mothers regarding effective breastfeeding methods, strategies to avoid neonatal hypoglycemia, and the various factors that heighten its likelihood. Additionally, healthcare professionals should emphasize the implementation of preventive measures to prevent this grave condition.